Passive smoking could still represent a risk factor in Mexican children with asthma - Pinedo Pichilingue, Aranza (2014)
We have read with interest the article by Bedolla et al. [1] and we believe the lack of association between passive smoking and asthma might be a consequence of the way the variable was measured. They defined passive smoking as follows: “smoking was considered as passive when one or more cigarettes were consumed by one or by both parents in the presence of the children”. We would like to highlight some factors that could have been taken into count when defining this variable: time of smoking, frequency and number of cigarettes.